PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAN PENGELOLAAN SUMBER DAYA MANUSIA (BKPSDM) KABUPATEN LAMPUNG TENGAH - Susana Susana; Afdal Mazni; Dharmawan Dharmawan (Universitas Muhammadiyah Metro, 2020)
The aim of this research were to determine the Effect of Motivation and Employee Competence on Employee Performance. This type of research using quantitative approaches and data collection techniques using questionnaires and observations. The population in this study were employees who worked at Staffing and Human Resource Development in Central Lampung Regency and were sampled by purposive sampling using the Slovin formula to 50 respondents. Data analysis using multiple linear regression analysis with the help of SPSS 21. Findings signify that: (1) Is work motivation significant to employee performance? (2) is competence significant for employee performance? (3) Does motivation and competence have a significant effect on employee performance?